A Comprehensive Systematic Review of The Association between the DASH Diet and Systolic Blood Pressure in Hypertensive Patients - Mohamad Fadli; Hendandy Driya Pamungkas (International Medical Journal Corp. Ltd, 2026)
Introduction: Hypertension is a major modifiable risk factor for cardiovascular disease worldwide. The Dietary Approaches to Stop Hypertension (DASH) diet has been recommended as an effective lifestyle intervention, but the magnitude of its effect on systolic blood pressure (SBP) in hypertensive patients varies across studies. This systematic review aims to comprehensively evaluate the association between the DASH diet and SBP reduction in hypertensive adults, identify effect modifiers, and provide context-specific clinical recommendations. Methods: A systematic review was conducted including randomized controlled trials, etc that examined the DASH diet in adults with hypertension (SBP ≥140 mmHg or on antihypertensive medication). Studies were screened based on predefined criteria including intervention duration ≥2 weeks and isolation of the DASH diet from major co-interventions. Data were extracted on study characteristics, DASH implementation, SBP outcomes, and effect modifiers. Results: Eighty studies were included, encompassing over 45,000 participants. The DASH diet consistently reduced SBP, with effects ranging from 3-16 mmHg depending on context. Controlled feeding trials demonstrated larger reductions (8-16 mmHg) compared to free-living implementations (3-6 mmHg). Baseline BP severity modified effects: patients with SBP ≥150 mmHg achieved up to -20.8 mmHg reduction with combined low-sodium DASH. The DASH diet enhanced the BP-lowering effects of RAS inhibitors, with reductions up to -9.5 mmHg in medicated patients. Sodium restriction produced additive effects, with the DASH-sodium combination achieving 84% BP control. Mechanistic studies revealed early natriuretic effects and later improvements in nitric oxide bioavailability. Discussion: The heterogeneity in SBP reduction reflects differences in study design, adherence levels, and patient characteristics rather than inconsistency in the diet's efficacy. Controlled feeding studies establish physiological maximum effects, while real-world implementations reflect practical effectiveness. The diet demonstrates particular efficacy in isolated systolic hypertension, older adults, and patients on RAS inhibitors. Conclusion: The DASH diet is a highly effective intervention for reducing SBP in hypertensive patients, with effects comparable to single-drug therapy in some populations. Implementation strategies should prioritize adherence support and cultural adaptation to maximize real-world effectiveness.